Prevalence and Antibiotic Resistance Pattern of Streptococcus, Staphylococcus, Neisseria meningitidis and Enterobacteriaceae in Two Reference Hospitals of Yaoundé: An Overview before and during COVID-19 Pandemic Era - Cecile Ingrid Djuikoue; Willy Yamdeu Djonkouh; Cavin Epie Bekolo; Rodrigue Kamga Wouambo; Raspail Carrel Founou; Paule Dana Djouela Djoulako; Gilder Tonfak Temgoua; Benjamin D. Thumamo Pokam; Nicolas Antoine-Moussiaux; Teke R. Apalata (MDPI AG, 2023)
The COVID-19 pandemic led to tremendously use of antimicrobial due to the lack of proper treatment strategies, raising concerns about emergence of antimicrobial resistance (AMR). This study aimed at determining the prevalence and antibiotic resistance pattern of selected bacteria isolates in 02 referral health facilities in Yaoundé before and during the COVID-19 pandemic era. We conducted a retrospective study over a period of 03 years (from 1 January 2019 to 31 December 2021) in the bacteriology units of the Central and General Hospitals of Yaoundé, Cameroon. Data on bacteria genera (Streptococcus, Staphylococcus, Neisseria meningitidis and Enterobacteriaceae) as well as their corresponding specifics antibiotics: Cefixime, azythromycin and erythromycin were obtained from laboratory records. The global resistance rate of bacteria as well as their correlation with antibiotics according to COVID-19 pandemic era was determined and compared. For p < 0.05, the difference was statistically significant. In all, 426 bacterial strains were included. It appeared that the highest number of bacteria isolates and lowest rate of bacterial resistance were recorded during the pre-COVID-19 period in 2019 (160 isolates vs. 58.8% resistance rate). Conversely, lower bacteria strains but greater resistance burden were recorded during the pandemic era (2020 and 2021) with the lowest bacteria amount and peak of bacteria resistance registered in 2020, the year of COVID-19 onset (120 isolates vs. 70% resistance in 2020 and 146 isolates vs. 58.9% resistance in 2021). In contrast to almost all others groups of bacteria where the resistance burden was quite constant or decreasing over years, the Enterobacteriaceae exhibited greater resistance rate during the pandemic period [60% (48/80) in 2019 to 86.9% (60/69) in 2020 and 64.5% (61/95) in 2021)]. Concerning antibiotics, unlike erythromycin, azythromycin related resitance increased during the pandemic period and the resistance to Cefixim tends to decrease the year of the pandemic onset (2020) and re-increase one year therafter. A significant association was found between resistant Enterobacteriaceae strains and cefixime (R = 0.7; p = 0.0001) and also, between resistant Staphylococcus strains and erythromycin (R = 0.8; p = 0.0001). These retrospective data showed a herogeneous MDR bacteria rate and antibiotic resistance pattern over time before and during the COVID-19 pandemic era suggesting that antimicrobial resistance needs to be more closely monitored.